Insights on Mineralogy and Chemistry of Fairview Gold Mine, Barberton Greenstone Belt, South Africa - Mohammed Alnagashi Hassan Altigani (Indonesian Journal on Geoscience, 2021)
DOI: 10.17014/ijog.8.1.73-99Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) and electron microprobe analysis (EMPA) techniques were used to determine the mineralogy and chemistry of dominant sulphide and associated gold deposits at the Fairview Gold Mine of the Barberton Greenstone Belt (BGB). The rocks and ore mineral associations at the Fairview Mine indicate mesothermal (orogenic) conditions for the gold deposit. The whole rock chemistry of the Fairview Mine reflects calc-alkaline affinities, and felsic provenance is revealed by high SiO2, K2O, Al2O3, and TiO2, and low Fe2O3, MgO, Ni, and Cr contents. The mineral assemblages of the Fairview Mine rocks and ores indicate three phases of metamorphisms; regional prograde, thermal, and retrograde metamorphism, which caused zonation and heterogeneity of the ore minerals. The principal ore minerals in this deposit are pyrite, arsenopyrite, pyrrhotite, chalcopyrite, and rare sphalerite, as well as minor gold. The obtained results revealed that sulphides of the Fairview Mine are divided into two types (generations) varying in their morphology, association, and elemental composition. The old type 1 is porous, anhedral, heterogeneous, contains inclusions and rich in As, Ni, Co, and Au compared to type 2. Trace-element distribution and occurrence mode of gold at Fairview mine reflect two phases of gold mineralization. The first stage is associated with sulphides (mainly pyrite and arsenopyrite), whilst the second phase is free-lode hosted by silicates (mainly quartz).